Pengelompokkan Provinsi Berdasarkan Indeks Demokrasi Indonesia Menggunakan Metode K-Means - Tiara Erlani Putri; Suwanda (UNISBA Press, 2024)
Abstract. Indonesia is a country that implements a democratic political system in its governance. The historical journey of democracy in Indonesia has proven that democracy is not always implemented as it should be. In reality, with each change in the democratic system in Indonesia, the role of the government becomes very dominant over the democratic system. Meanwhile, the people, as the holders of the country's sovereignty, are forced to follow the power holders in implementing democracy. Indonesian Democracy Index is a measurement tool used to assess how well democracy functions. Indonesian Democracy Index is an effort to measure Indonesia's democracy through three aspects: Freedom, Equality, and the Capacity of Democratic Institutions. This study aims to classify provinces in Indonesia based on the quality of the Indonesian Democracy Index (IDI) for the year 2022. K-Means method is used to cluster the provinces into several groups, taking into account the aspects of freedom, equality, and the capacity of democratic institutions. The silhouette method is used to determine the optimal number of clusters. The analysis results show that the provinces can be classified into two clusters, with Cluster 1 consisting of 25 provinces and Cluster 2 consisting of 9 provinces. Abstrak. Indonesia adalah negara yang menerapkan sistem politik demokrasi dalam pemerintahannya. Perjalanan sejarah demokrasi di Indonesia telah membuktikan bahwa tidak selamanya demokrasi dilaksanakan sesuai dengan seharusnya. Pada kenyataannya setiap berganti sistem demokrasi di Indonesia, peranan pemerintah sangat dominan terhadap sistem demokrasi di Indonesia. Sementara rakyat sebagai pemegang kedaulatan negara dipaksa untuk mengikuti para pemangku kekuasaan dalam menjalankan demokrasi. Indeks Demokrasi Indonesia adalah alat pengukuran yang digunakan untuk menilai sejauh mana demokrasi itu berfungsi. Indeks Demokrasi Indonesia merupakan salah satu bentuk upaya untuk mengukur demokrasi Indonesia melalui tiga aspek: Kebebasan, Kesetaraan, dan Kapasitas Lembaga Demokrasi. Penelitian ini bertujuan untuk mengelompokkan provinsi di Indonesia berdasarkan kualitas Indeks Demokrasi Indonesia (IDI) tahun 2022. Metode K-Means digunakan untuk mengelompokkan provinsi menjadi beberapa cluster, dengan mempertimbangkan aspek kebebasan, kesetaraan, dan kapasitas lembaga demokrasi. Metode silhouette digunakan untuk menentukan jumlah cluster yang optimal. Hasil analisis menunjukkan bahwa provinsi-provinsi dapat diklasifikasikan menjadi dua cluster. Dengan cluster 1 diperoleh sebanyak 25 Provinsi serta pada cluster 1 diperoleh sebanyak 9 Provinsi